2018
DOI: 10.1103/physrevmaterials.2.064005
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic thermal transport in bulk hexagonal boron nitride

Abstract: Hexagonal boron nitride (h-BN) has received great interest in recent years as a wide bandgap analog of graphene-derived systems, along with its potential in a wide range of applications, for example, as the dielectric layer for graphene devices. However, the thermal transport properties of h-BN, which can be critical for device reliability and functionality, are little studied both experimentally and theoretically. The primary challenge in the experimental measurements of the anisotropic thermal conductivity o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
108
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(123 citation statements)
references
References 68 publications
12
108
2
1
Order By: Relevance
“…Defects in hBN with ZPLs near 2.21 eV remain poorly classified 16 , but the results discussed here are relevant to broad classes of defects in hBN. Phonon sidebands were observed redshifted by 166, 177, 200, 326, 343, 359 and 395 meV from the ZPL in agreement with experimental and ab initio calculations of the phonon dispersion for hBN [17][18][19][20][21] .…”
supporting
confidence: 83%
“…Defects in hBN with ZPLs near 2.21 eV remain poorly classified 16 , but the results discussed here are relevant to broad classes of defects in hBN. Phonon sidebands were observed redshifted by 166, 177, 200, 326, 343, 359 and 395 meV from the ZPL in agreement with experimental and ab initio calculations of the phonon dispersion for hBN [17][18][19][20][21] .…”
supporting
confidence: 83%
“…Raising the temperature excites a larger number of energy states and also shifts thermal energy peak towards higher frequencies according to the Wien's displacement law, which will be further discussed. We notice that the measured thermal conductivity at 300 K is in good agreement with the literature data . At this temperature, the radiative contribution is relatively small.…”
Section: Resultssupporting
confidence: 90%
“…Given these considerations, the extracted k Phonon,exp is in a reasonable agreement with the expected 1/ T trend. On the other hand, we also notice a recent study on the out‐of‐plane thermal conductivity of hBN which showed that thermal conductivity does not follow 1/ T in a temperature range between over 100 and 400 K . This deviation was attributed to the contribution of high‐frequency acoustic phonons which do not follow the 1/ T trend at temperatures below 400 K. At temperatures above 400 K, however, the contribution of high‐frequency phonons also decreases with temperature, resulting in ≈1/ T trend in phonon thermal conductivity.…”
Section: Resultsmentioning
confidence: 45%
See 1 more Smart Citation
“…19 The uncertainties of Kz, K||(θ) and G are then estimated using a multivariate error propagation formalism based on Jacobi matrices, which was first developed by Yang et al 20 and widely used in some related works. [21][22][23][24] The effect of the signal noise, manifested as the standard deviation σ between the measured data points and the thermal model prediction, is also included in the estimated uncertainty. Figure 1(d) shows that from a typical elliptical-beam TDTR measurement, Kz and K||(θ) of β-Ga2O3 can usually be determined with an uncertainty of 11% and 15%, respectively.…”
Section: Textmentioning
confidence: 99%